Epigenetics of melanoma: implications for immune-based therapies. (October 2013) - Fratta, Elisabetta; Sigalotti, Luca; Covre, Alessia; Parisi, Giulia; Coral, Sandra; Maio, Michele
Malignant melanoma is a complex disease that arises and evolves due to a myriad of genetic and epigenetic events. Among these, the interaction between epigenetic alterations (i.e., histone modifications, DNA methylation, mRNA silencing by miRNAs and nucleosome repositioning) has been recently identified as playing an important role in melanoma development and progression by affecting key cellular pathways such as cell cycle regulation, DNA repair, apoptosis, invasion and immune recognition. Differently to genetic lesions, epigenetic changes are potentially pharmacologically reversible by using epigenetic drugs. Along this line, preclinical and clinical findings indicate that these drugs, given alone or in combination therapies, can efficiently modulate the immunophenotype of melanoma cells. The aim of this review is to provide a comprehensive summary of melanoma epigenetics and the current use of epigenetic drugs in the clinical setting.